Pengaruh Agresivitas Pajak, Profitabilitas, Leverage, Dan Dewan Komisaris Independen Terhadap Corporate Social Responsibility Disclosure Dengan Ukuran Perusahaan Sebagai Variabel Moderasi : (Pada Perusahaan Sektor Infrastruktur Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2021) - Indra Gunawan Siregar; Khorida AR; Hikmah Putri Hastuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to determine the effect of tax aggressiveness, profitability, leverage, and an independent board of commissioners on corporate social responsibility disclosure with company size as a moderating variable in infrastructure companies listed on the Indonesia Stock Exchange. The period used in this research is 4 years, starting from 2018-2021. This study uses a quantitative approach. The population in this study were 67 infrastructure companies that were still listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling and a sample of 13 companies was obtained. The data analysis technique used is moderated regression analysis (MRA). The results of the research show that partially tax aggressiveness, company size has a positive effect on corporate social responsibility disclosure, profitability, leverage, an independent board of commissioners has no effect on corporate social responsibility disclosure, company size is able to moderate tax aggressiveness towards corporate social responsibility disclosure, and company size does not. able to moderate profitability, leverage, independent board of commissioners on corporate social responsibility disclosure. Simultaneously, tax aggressiveness, profitability, leverage, independent board of commissioners, and company size have a positive and significant effect on corporate social responsibility disclosure. The ability of the variables tax aggressiveness, profitability, leverage, board of commissioners and company size to explain Corporate Social Responsibility disclosure is 21% as shown by the large adjusted R square value. Meanwhile, the remaining 79% is influenced by other variables.